Theoretical foundations for managing service organizations in the context of digital transformations - E. S. Gusar; I. N. Primyshev (Омский научный вестник: Серия "Общество. История. Современность", 2023)
The aim of the investigation is to study the theoretical foundations of the management of service organizations in the context of digital transformations. The authors reviewed and clarified such concepts as «digital economy» and «digital transformation». A number of reasons have been identified that cause changes in the theoretical foundations of managing service organizations in the context of digital transformations. It is noted that the main goal of managing service sector organizations in the context of digital transformations is to ensure the effective functioning of service sector organizations in the long term. The key elements of the formation of an effective management system for the organization of the service sector in the context of digital transformations are presented in more detail. The authors propose methods and principles for managing service organizations in the context of digital transformations. The key elements of management of service sector organizations in the context of digital transformations are identified. It is concluded that the application of the principles and methods of managing organizations in the service sector in the context of digital transformations aims to achieve tactical (short-term) and strategic (long-term) goals of the organization of the service sector, as well as increasing the efficiency of its functioning by minimizing unnecessary and unjustified costs and ensuring profit growth.